2022
DOI: 10.1002/pc.27057
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of MOF‐Zn@ZnO composite and its properties in SBR

Abstract: The synthesis and application of metal-organic skeleton materials (MOFs) have attracted much attention in recent years due to their special structures and properties. In order to expand the application field of MOFs materials, this paper designed experiments to explore the application prospect of MOFs materials in the field of rubber. In this study, zinc acetate dihydrate was used as the central metal ion source, terephthalic acid as organic ligand and deionized water as solvent. MOF-Zn was prepared by hydroth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The figure displays that the interfacial layer withstanded concentrated destruction before fiber debonding during the fatigue test, which formed a severely damaged interface layer. Because the interface bonding was effectively improved by the VPL coating treatment, and the fibers were stripped from the matrix owing to fatigue, the long HF could absorb more strain energy during the fatigue‐fracture process and was severely damaged, this prevented excessive fatigue damage to the SBR matrix and improved the fatigue life of the compounds 61,62 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The figure displays that the interfacial layer withstanded concentrated destruction before fiber debonding during the fatigue test, which formed a severely damaged interface layer. Because the interface bonding was effectively improved by the VPL coating treatment, and the fibers were stripped from the matrix owing to fatigue, the long HF could absorb more strain energy during the fatigue‐fracture process and was severely damaged, this prevented excessive fatigue damage to the SBR matrix and improved the fatigue life of the compounds 61,62 …”
Section: Resultsmentioning
confidence: 99%
“…Because the interface bonding was effectively improved by the VPL coating treatment, and the fibers were stripped from the matrix owing to fatigue, the long HF could absorb more strain energy during the fatigue-fracture process and was severely damaged, this prevented excessive fatigue damage to the SBR matrix and improved the fatigue life of the compounds. 61,62…”
Section: Analysis Of Uniaxial Tensile Fatigue Life Of Gaped Samplesmentioning
confidence: 99%
“…Joseph and his co‐authors 20 proved NH 2 ‐MIL‐53(Al) as reinforcing filler was favorable for the enhanced entanglement of styrene‐butadiene rubber (SBR) chains at the interface so that the thermal and dynamic mechanical properties of SBR‐MOF were superior to SBR‐Al 2 O 3 composite. Lei et al 21 reported in‐situ growth of ZnO nanoparticles on the surface of MOF‐Zn and mentioned that as prepared MOF‐Zn@ZnO promoted the vulcanization of SBR due to the inhibition of agglomeration of ZnO nanoparticles by MOF‐Zn. However, there is still a blank in the influence of the intrinsic structure of MOFs on rubber vulcanization.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs), promising nanoporous coordination materials, are new crystalline polymers of metal ions or metal clusters coupled with organic ligands. 14 The tunable nanoscale pore structure, flexibility for modification, large specific surface area (SSA), and unsaturated metal sites make them highly intriguing. 15,16 Nonetheless, several MOF-based materials demand more intricate organic linkers and rigorous reaction conditions that impede their practical usage and large-scale production.…”
mentioning
confidence: 99%
“…15,16 Nonetheless, several MOF-based materials demand more intricate organic linkers and rigorous reaction conditions that impede their practical usage and large-scale production. 14 ZIF-67, a vital subclass of MOFs, is one of the most widely studied ZIF materials, which can be conveniently synthesized with minimal cost, offering high potential for practical applications. 17,18 Unique features of ZIF-67 include its excellent hydrothermal stability, great SSA, and intriguing physicochemical properties, making it a good contender for large-scale applications in water purification, separation, and gas adsorption.…”
mentioning
confidence: 99%